LITHOLOGICAL AND MINERALOGICAL COMPOSITION OF ACCUMULATIVE BEACH SEDIMENTS OF THE DNIESTER-DNIPRO SEGMENT OF THE BLACK SEA - NESTEROVSKYI, Viktor; DEIAK, Mykhailo; TARNOVETSKYI, Andrii (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article presents the results of studies of modern beach sediments of the northwestern Black Sea coast from the village of KarolinoBuhaz (Odesa oblast) to the village of Rybakivka (Mykolaiv oblast). The length of the coastal zone is about 110 km. Most of the beaches here are sloping beaches of various morphologies and widths. Using a uniform methodology, 64 samples were collected and processed along the entire profile. The sampling was carried out from the middle part of the beach strip between the water's edge and the shore in the summer in the absence of storms from a depth of 30 cm. The area of the sweep was 30×30 cm. Each sampling point was accompanied by a description of the geological structure, condition of the coastal zone and characteristics of the beach area. The sampling points were georeferenced using a GPS system. Grain size and mineralogical analyses were carried out, and the main patterns of lithological composition and distribution of mineral fractions along the entire profile were established. Several contrasting areas were identified: 1) Karolino-Buhaz-Chornomorsk, where the medium-grained (0.5–0.25 mm) fraction significantly prevails (67 %). In the sediments of this area, the main mineral of all fractions is quartz (90 %). The dominant heavy minerals are garnet, ilmenite, and magnetite; 2) Chornomorsk – Cape Velykyi Fontan and Lanzheron (Odesa oblast) – Kobleve (Mykolaiv oblast) with a significant content of coarse-grained psamite (2–1 mm) – 29 % and gravel (2–5 mm) – 16 % fractions. The main minerals here in all fractions are quartz and calcite; 3) Cape Velykyi Fontan -Lanzheron is characterised by a variable particle size distribution, with the bulk represented by fractions of 0.25–0.5 mm and 0.25–0.1 mm, which have different proportions on different beaches. The dominant mineral in all fractions is quartz, with calcite detritus present in subordinate amounts. Heavy minerals are represented by single grains of garnet, ilmenite, magnetite, staurolite; 4) Kobleve – Rybakivka (Mykolaiv oblast) with an increase in the content of fractions of 0.25–0.1 mm (up to 42 %). The main mineral in all fractions is quartz (up to 87 %). The secondary component is calcite detritus. Biotite, muscovite and tourmaline are notable impurities in fine-grained fractions. On some beaches located near the seaport of Odesa, numerous glassy spheroidal aggregates of various compositions and ferruginous spheroids have been found in fractions of less than 0.5 mm. In places of concentration of such formations, the colour of the beach sediments becomes grey. The total content of anthropogenic material in the beach sediments of the studied segment is on average 0.1–0.12 %. It increases significantly (up to 0.23 %) in the vicinity of the port of Odesa and adjacent areas. In addition, in contrast to the Danube-Dniester segment, there is a noticeable increase in the amount of large-sized material of man-made origin (plastic, concrete, bricks, wood fragments, metal, fabric, etc.) in the beach area. The main factor in the formation of the mineral and particle size distribution of beach sediments in the Dniester-Dnipro segment of the coast is coastal abrasion. The role of terrigenous inputs from the land is minimal and is manifested only in the northern part (Berezan Bay area). The formation of the material and fractional composition is significantly influenced by periodic artificial sand alluviation (beach area of the Odesa agglomeration), strengthening of slopes with concrete blocks, piling up of blocks of igneous and metamorphic rocks, mainly granitoid, breakwaters and other structures that change the direction and influence along the coastal currents.
Keywords: Black Sea; Dniester-Dnipro segment; lithological and mineralogical composition; beach sediments